Capacity development of Madurese female farmers in the implementation of integrated crop management in corn - Teti Sugiarti; Nurul Arifiyanti; Meidiana Purnamasari; Wen Chi Huang (Agriekonomika, 2022)
Women as housewives have a big role in managing their family economy. This study aims to: 1. Analyze the level of awareness of gender equality among female corn farmers, 2. Analyze levels of knowledge, attitude, and skill of female farmers in terms of PTT in corn, 3. Analyze the empowerment process, results, and impacts obtained by female corn farmers from farming school. The study was conducted in three regencies of Madura, namely Bangkalan, Sampang, and Pamekasan. Data were analyzed using descriptive quantitative analysis to answer the first and second objectives, and PAR analysis to answer the third question. Based on the results of the study, women’s role is more dominant than men in several aspects. Some of them are activities in finance, post-harvest, and others. The majority of farmers adopt corn farming methods based on experiences from generations. Empowerment activities such as FGD and training have benefited female farmers.